2016
DOI: 10.1073/pnas.1604613113
|View full text |Cite
|
Sign up to set email alerts
|

Directional amorphization of boron carbide subjected to laser shock compression

Abstract: Solid-state shock-wave propagation is strongly nonequilibrium in nature and hence rate dependent. Using high-power pulsed-laserdriven shock compression, unprecedented high strain rates can be achieved; here we report the directional amorphization in boron carbide polycrystals. At a shock pressure of 45∼50 GPa, multiple planar faults, slightly deviated from maximum shear direction, occur a few hundred nanometers below the shock surface. High-resolution transmission electron microscopy reveals that these planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 35 publications
4
69
1
1
Order By: Relevance
“…The increase in temperature due to shock compression can be evaluated by considering both the homogeneous temperature rise (ΔT homo ) resulting from work done by hydrostatic pressure and the localized temperature rise (ΔT local ) resulting from work done by shear stress. The latter assumes a balance between relaxation of deviatoric strain energy and decrease in internal energy with heat loss to its surroundings, and thus gives a rough estimate of the temperature inside the amorphous band (19):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in temperature due to shock compression can be evaluated by considering both the homogeneous temperature rise (ΔT homo ) resulting from work done by hydrostatic pressure and the localized temperature rise (ΔT local ) resulting from work done by shear stress. The latter assumes a balance between relaxation of deviatoric strain energy and decrease in internal energy with heat loss to its surroundings, and thus gives a rough estimate of the temperature inside the amorphous band (19):…”
Section: Discussionmentioning
confidence: 99%
“…The short duration of the stress pulse and impedancematched encapsulation preserves the integrity of the target by suppressing the full development of cracks and enables postshock microstructure characterization. Using this methodology, we have previously reported shock-induced amorphization in silicon (18) and boron carbide (19). Before that, Jeanloz et al (20) discovered this phenomenon in olivine (iron/magnesium silicate) subjected to shock compression.…”
mentioning
confidence: 98%
“…Later, Chen et al [2] identified this deformation mechanism as localized amorphization (loss of crystalline order) by conducting transmission electron microscopy (TEM) of small fragments of B 4 C armor plates subjected to ballistic impact. Since then, this mechanism has been observed under indentation [3][4][5], ballistic impact [2,6], laser shock [7], diamond anvil cell [8], mechanical scratching [9], electric fields [10], and radiation [11]. Numerous characterization techniques, such as TEM [2,7], Raman spectroscopy [4,[12][13][14], photoluminiscence [14], FTIR [14], EELS [2], and neutron scattering [3], have been employed to observe the structure of the amorphized region.…”
mentioning
confidence: 99%
“…Since then, this mechanism has been observed under indentation [3][4][5], ballistic impact [2,6], laser shock [7], diamond anvil cell [8], mechanical scratching [9], electric fields [10], and radiation [11]. Numerous characterization techniques, such as TEM [2,7], Raman spectroscopy [4,[12][13][14], photoluminiscence [14], FTIR [14], EELS [2], and neutron scattering [3], have been employed to observe the structure of the amorphized region. The consequences of amorphization include reduced ballistic performance [2], loss of hardness under dynamic loads [14][15][16], post-HEL softening [1], and change in electrical properties [10].…”
mentioning
confidence: 99%
“…These anomalies in the high-pressure performance of boron carbide spurred numerous investigations into the evolution of short-range disorder in the material, often referred to as "amorphization". Subsequent studies have also documented amorphization under Berkovich [8][9][10][11] and Vickers 3,12-16 indentations, laser shock impact, 17 mechanical scratching, 9,18 and nonhydrostatic loading in diamond anvil cell experiments. 19 Postmortem TEM of the deformed regions revealed inhomogeneous distributions of nanoscale amorphized zones within the crystalline matrix of boron carbide.…”
Section: Introductionmentioning
confidence: 93%